Impact of policy regulations on the functioning of hospitals in Poland during the COVID-19 pandemic: A qualitative analysis - Dariusz Masłowski; Ewa Kulińska; Mariusz Salwin; Karolina Pawlas; Karolina Kulińska-Jachowska (International Journal of Management and Economics, 2022)
During the state of epidemic in Poland in 2020, all facilities providing medical services were subject to constant reorganization. Legal changes, which were introduced at a very rapid pace, did not allow the standardization of the work of the health service. Therefore, the assessment of the practical effects of the introduced legal measures is challenging due to the lack of fixed benchmarks. Accordingly, the research method used in the article is a survey conducted among employees of the Voivodeship Specialist Hospital in December 2020, in which 165 employees from different wards participated. For this purpose, the article presents the detailed description of policy regulations related to healthcare management introduced in Poland in 2020. Combining legal research and qualitative data allowed general conclusions to be drawn with regard to the quality assessment of the implemented policy measures from the perspective of healthcare professionals.
Keywords: K39; I11; I12; I15; I18; 650; COVID-19 pandemic; hospitals; legal regulations; management processes